Competition between H2O and CO2 during the gasification of Powder River Basin coal. (1st January 2017) - Wang, Ying; Bell, David A.
Highlights: The reaction rate of Powder River Basin coal gasification in CO2 and H2 O gas mixture was measured. Langmuir–Hinshelwood models were used to describe both reaction kinetics and degree of surface saturation. H2 O molecules primarily occupy active sites when H2 O and CO2 are both present. A steam-dominating competition model was presented and matched with experimental results. Abstract: Reaction kinetics of Powder River Basin coal gasification were measured in a modified drop tube fixed bed reactor, accompanied with a rapid response, real-time gas analysis system. The material was rapidly heated and quickly pyrolyzed, followed by a slow gasification with long residence time. Tests are done at 833 °C and elevated pressure to 4 atm. The conditions were chosen to minimize mass transfer restrictions, so that only surface reactions were measured. The experimental data was fitted using Langmuir-Hinshelwood models to describe both reaction kinetics and degree of surface saturation. CO2 addition into steam gasification, steam addition into CO2 gasification, and injection of steam into an in-progress CO2 gasification test were performed. We found a rarely observed competition mechanism, in which H2 O molecules primarily occupy active sites when H2 O and CO2 are both present. With sufficient steam partial pressure, the reaction rate in mixtures of H2 O and CO2 is equal to steam reaction rate. A newly developed L-H type model was presented to describe this competition mechanism. This model contains a steam reaction rate term and a supplementary CO2 reaction rate term, and matches our experimental results.